2020
DOI: 10.5194/hess-24-1159-2020
|View full text |Cite
|
Sign up to set email alerts
|

Recession analysis revisited: impacts of climate on parameter estimation

Abstract: Abstract. Recession analysis is a classical method in hydrology to assess watersheds' hydrological properties by means of the receding limb of a hydrograph, frequently expressed as the rate of change in discharge (-dQ/dt) against discharge (Q). This relationship is often assumed to take the form of a power law -dQ/dt=aQb, where a and b are recession parameters. Recent studies have highlighted major differences in the estimation of the recession parameters depending on the method, casting doubt on our ability t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…Recession analysis has been used extensively to quantify the drainage behavior of catchments (Brutsaert & Nieber, 1977; Jachens et al, 2020; Tashie et al, 2020; Roques et al, 2017). It is often assumed that the relationship between the rate of change of streamflow and streamflow follows a power law.…”
Section: Methods and Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recession analysis has been used extensively to quantify the drainage behavior of catchments (Brutsaert & Nieber, 1977; Jachens et al, 2020; Tashie et al, 2020; Roques et al, 2017). It is often assumed that the relationship between the rate of change of streamflow and streamflow follows a power law.…”
Section: Methods and Data Setsmentioning
confidence: 99%
“… normaldQnormaldt=αQβ where α and β m are parameters that can be obtained by fitting Equation to recession data. There are numerous methodological choices that can impact the resulting parameter values (e.g., Dralle et al, 2017; Jachens et al, 2020; Stoelzle et al, 2013). We extract recession segments that are strictly decreasing ( normaldQnormaldt<0), remove the first day, and only keep recession segments of 5 days or longer (Jachens et al, 2020).…”
Section: Methods and Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering drought resilience, comparing b values for high and low flows can be used to identify a change in hydraulic regime and using b values at low flows to indicate a watershed's sensitivity to climate change. Where b increases as Q decreases, streamflow becomes more stable, or sustained, at low flows and may indicate watersheds that are less sensitive to drought (Berghuijs et al, 2016; Jachens et al, 2020). In this case, b values are larger at low flows than at high flows.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, observations reveal large variability in recession behavior, including cases where b is larger at lower Q than at higher Q (e.g., Clark et al, 2009; Mutzner et al, 2013; Rupp & Selker, 2006a), inconsistent the aforementioned hydraulic theory. Recent studies have suggested that such cases are common (Jachens et al, 2020; Tashie et al, 2020). In contrast, if b decreases as Q decreases, this indicates that streamflow is more stable, or sustained, at high flows while streamflow declines at a faster rate at low flows.…”
Section: Introductionmentioning
confidence: 99%